ISOLATION AND CHARACTERIZATION OF HEXACHLOROCYCLOHEXANE DEGRADATION OF FILAMENTOUS FUNGAL STRAIN FNA33 FROM PESTICIDE DETOXIFICATION BY AEROBIC BIOREACTOR - Hà, Đặng Thị Cẩm (Vietnam Journal of Biotechnology, 2011)
Three filamentous fungal sfrains were isolated of soil bioremediation freatment by aerobic bioreactor in order to detoxify DDT, HCH and other pesticides. These fimgal strains FNA31, FNA32 and FNA33 cultivated in mineral salt medium containing 300 ppm HCH and FNA33 showed the best grovrth. Based on colony morphology, sporephore observed through microscope and sequence of a partial 18S rRNA gene, the sfrain FNA33 could be classified Aspergillus sp. FNA33. The 18S rRNA gene fragment sequence oi Aspergillus sp. FNA33 was deposited in the GenBank database with assession number EU684231. After 14 days incubation in mineral salt medium containing 0.5% glucose, Aspergillus sp. FNA33 degraded 88% HCH with initial concenfration 243 ppm. Furthermore, after 7 days in the same condition this sfrain also produced exfracellular enzyme mangan peroxidase (434.5 U/l) and laccase (4.3 U/l). After 20 days of cultivation the activity of manganese peroxidase detected still at high level (269 U/l)